Reference values and repeatability of pulsed-wave Doppler flowmetry of portal vein in healthy dromedary she-camels - Elsayed, Ahmed A; Gomaa, Naglaa A (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was conducted to establish the normal values and repeatability of pulsed-wave (PW) Doppler ultrasonographic parameters of the hepatic portal circulation in healthy dromedary she-camels. Materials and Methods: According to the American Society of Veterinary Clinical Pathology guidelines, the sample size and statistical analysis were followed. Ten healthy, non-pregnant, non-lactating she-camels were selected after physical, hematological, and ultrasonographic examinations. All hepatic ultrasonographic measurements were obtained from unsedated standing she-camels at the 11th right intercostal space using B-mode and PW Doppler. Results: The ultrasonographic measurements were portal vein (PV) diameter 1.76 ± 0.37 cm; portal velocity 12.3 ± 3.2 cm/sec; portal area 2.05 ± 0.57 (cm)²; portal congestion index 0.16 ± 0.04 cms; and portal blood flow volume 0.02 ± 0.05 ml/sec/kg. The intra-assay coefficient of variations (CV)% of the above-mentioned variables were 5.84 ± 4.32, 12.3 ± 7.1, 10.5 ± 5.8, 14.7 ± 7.1, and 15.8 ± 12, respectively. However, the inter-assay CV% were 13.2 ± 5.9, 18.5 ± 8.4, 19.7 ± 7.6, 17.3 ± 8.8, and 31.9 ± 15, respectively. Conclusion: This study provides data that may be used as reference values for Doppler measurements of the PV in she-camels, which may help diagnose some hepatic disorders in camels. J. Adv. Vet. Anim. Res., 7(3): 698-703, Dec 2020